2018
DOI: 10.1111/tbed.12866
|View full text |Cite
|
Sign up to set email alerts
|

Bovine anaplasmosis and tick-borne pathogens in cattle of the Galapagos Islands

Abstract: A cross-sectional study was conducted to determine the species of Anaplasma spp. and estimate its prevalence in cattle of the three main cattle-producing Galapagos Islands (Santa Cruz, San Cristóbal and Isabela) using indirect PCR assays, genetic sequencing and ELISA. Ticks were also collected from cattle and scanned for 47 tick-borne pathogens in a 48 × 48 real-time PCR chip. A mixed effects logistic regression was performed to identify potential risk factors explaining Anaplasma infection in cattle. A. phago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Previous studies in Ecuador demonstrated the presence of Babesia spp. in ticks, but not in cattle [16,18]. Our study shows for the first time B. bovis and B. bigemina in two geographical areas El Carmen and Quito, with a prevalence of 18.93% and 20.28%, respectively for Babesia spp.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Previous studies in Ecuador demonstrated the presence of Babesia spp. in ticks, but not in cattle [16,18]. Our study shows for the first time B. bovis and B. bigemina in two geographical areas El Carmen and Quito, with a prevalence of 18.93% and 20.28%, respectively for Babesia spp.…”
Section: Discussionmentioning
confidence: 58%
“…(21%) [16]. In addition, molecular tests as Polymerase Chain Reaction (PCR) and quantitative polymerase chain reaction (qPCR) demonstrated the presence of B. bovis, B. bigemina, and mixed infections in ticks (R. microplus) [16][17][18]. On the contrary, the use of a PCR test using ribosomal 18s as a target (PCR) with primers described by Carret et al, 1999 [19], did not demonstrate the presence of Babesia spp.…”
Section: Introductionmentioning
confidence: 99%
“…was identified in hard ticks (Amblyomma and Rhipicephalus sp.) in Ethiopia [81,82], Mali [18], Côte d'Ivoire [60], Egypt [17], Madagascar [83] and Ecuador [77]. In the present study, a new potential B. theileri was identified in two Rh.…”
Section: Discussionmentioning
confidence: 49%
“…B. theileri in Rh. microplus has been reported in Madagascar [83], Ecuador [77], Brazil [84] and Argentina [85]. Thus, this is the first time that B. theileri has been detected in Rh.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation